Pengembangan Bahan Ajar Ilmu Bayan Berbasis Analisis Kontrastif di Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Ilmu Al-Quran - Muhammad Ihsanuddin Masdar (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2019)
The students of Arabic Education at State Institute of Al-Qur’an study Ilmu Bayan in order to understand about the beauty and majesty of Al-Qur’an verses, language style, Arabic expression, and to compose the right and good sentences. But, in the fact, learning of Ilmu Bayan cannot comply all of those criterion. There are many problems in this case such as: Students have difficulties to remember the rules of Ilmu Bayan and they try to compare Ilmu Bayan study to Indonesian language study. The learned book is using Arabic language without any translation and it’s also dominated by Arabic poem which is difficult to understand. Based on those data, the researcher develops a teaching book based on contractive analysis.This research use qualitative and quantitative approach with research and development method. The result of this research are: 1 contrastive analysis between Ilmu Bayan style of language and Indonesian style of language, 2 Product, that is a teaching book of Ilmu Bayan for STIQ Amuntai students. So that the steps to arrange the book are: need analysis, collecting data, product design, validating product, revise product, expediency test of product, revise of expedience test of product, effectiveness test of product, revise product, 3 Teaching book arranged by researcher is effective in learning Ilmu Bayan, known by comparing control and experiment group posttest result, that is T counting (4,36) more than T table (1,71) and T table (2,42).